Paranormal : my life in pursuit of the afterlife - Moody, Raymond A., Jr (HarperOne, 2012)
Raymond Moody is the "grandfather" of the modern NDE (Near Death Experience) movement. In this account of his lifetime of research into the after life, Moody explains how he stumbled onto these amazingly consistent stories by people who had died and come back to life. Moody was the first scholar and doctor to describe the accounts of the bright light, the tunnel, the presence of loved ones waiting on the other side, past life review, and meeting heavenly beings--all of which have become part of our modern cultural knowledge.